2015
DOI: 10.1002/cld.498
|View full text |Cite
|
Sign up to set email alerts
|

Bone disease in cirrhosis

Abstract: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/6-4-reading-patel.htm a video presentation of this article http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/6-4-interview-munoz.htm the interview with the author https://wileyhealthlearning.com/Activity/3623832/Activity.aspx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…Shakibaei et al, observed alteration in trabecular pattern and changes in jaw bone density (16). The frequency of bone disease in cirrhotic patients was reported to be 12% to 55% by Patel et al (17). In the study by Dagistan et al, pathologic defects with ground-glass appearance were seen in the mandible (18).…”
Section: Introductionmentioning
confidence: 97%
“…Shakibaei et al, observed alteration in trabecular pattern and changes in jaw bone density (16). The frequency of bone disease in cirrhotic patients was reported to be 12% to 55% by Patel et al (17). In the study by Dagistan et al, pathologic defects with ground-glass appearance were seen in the mandible (18).…”
Section: Introductionmentioning
confidence: 97%
“…Major risk factors of bone disease in patients with cirrhosis include all risk factors of osteoporosis in the general population. Thus, female gender, advanced age, previous fragility fracture, poor nutritional status, limited physical activity, oral glucocorticoid therapy, low body mass index (<19), high alcohol intake, maternal history of hip fracture, smoking and malnutrition render particularly probable the diagnosis of osteoporosis in a cirrhotic patient [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…vitamin D deficiency, secondary hyperparathyroidism and hypogonadism are risk factors of osteoporosis of great relevance among cirrhotic patients 12,14 . After orthotopic liver transplantation (OLT), osteoporosis is the result of two parameters: preexisting osteopenia at OLT and rapid decline in bone mass in the post-transplantation period.…”
Section: Jrpmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation led us to further explore the pathogenesis of these altered pro‐osteoclastic and anti‐osteoclastic factors in advanced cirrhosis. Activation of inflammatory cells in patients with cirrhosis induces proinflammatory cytokine production, such as TNF‐α, IL‐1, IL‐13, IL‐6, IL‐7, IL‐11, IL‐15, and IL‐17 . These inflammatory mediators have been described to be elevated in advanced cirrhosis and promote osteoclast precursor activation or RANKL production by osteoblasts, which are associated with bone resorption .…”
Section: Discussionmentioning
confidence: 99%